Interleaved TMS/CASL: Comparison of different rTMS protocols - Moisa, Marius; Pohmann, Rolf; Uludağ, Kamil; Thielscher, Axel (NeuroImage (Orlando, Fla.), 2010)
Continuous Arterial Spin Labeling (CASL) offers the possibility to quantitatively measure the regional cerebral blood flow (rCBF). We demonstrate, for the first time, the feasibility of interleaving Transcranial Magnetic Stimulation (TMS) with CASL at 3 T. Two different repetitive TMS (rTMS) protocols were applied to the motor cortex in 10 subjects and the effect on rCBF was measured using a CASL sequence with separate RF coils for labeling the inflowing blood. Each subject was investigated, using a block design, under 7 different conditions: continuous 2 Hz rTMS (3 intensities: 100%, 110% and 120% resting motor threshold [MT]), short 10 Hz rTMS trains at 110% MT (8 pulses per train; 3 different numbers of trains per block with 2, 4 and 12 s intervals between trains) and volitional movement (acoustically triggered by 50% MT stimuli). We show robust rCBF increases in motor and premotor areas due to rTMS, even at the lowest stimulation intensity of 100% MT. RCBF exhibited a linear positive dependency on stimulation intensity (for continuous 2 Hz rTMS) and the number of 10 Hz trains in the stimulated M1/S1 as well as in premotor and supplementary motor areas. Interestingly, the 2 different rTMS protocols yielded markedly different rCBF activation time courses, which did not correlate with the electromyographic recordings of the muscle responses. In future, this novel combination of TMS with ASL will offer the possibility to investigate the immediate and after-effects of rTMS stimulation on rCBF, which previously was only possible using PET.